Florida Biosolids: Rules for Biosolids Classes - John Hallas; Ann C. Wilkie; Cheryl L. Mackowiak (EDIS)
Biosolids are the liquid, semisolid, and solid fractions of the treated waste stream from a domestic waste water treatment facility. This 5-page fact sheet, part of the Florida Biosolids series, provides an overview of biosolids, biosolids classes, pathogen reduction, vector attraction reduction, and metal contaminants, and also discusses the purpose, applicability, and history of Chapter 62-640, Florida Administrative Code. Written by John Hallas, Ann C. Wilkie, and Cheryl L. Mackowiak, and published by the UF Department of Soil and Water Science, December 2015.